IDENTIFIKASI KANDUNGAN CaCO3 DALAM BATUAN KAPUR DI DESA MANULAI I MENGGUNAKAN METODE XRF DAN XRD - Kristantia Mida Subah; Redi Kristian Pingak; Minsyahril Bukit; Albert Zicko Johannes (Universitas Nusa Cendana, 2023)
This study aims to determine the compounds contained in limestone, identify the content and crystal phase of CaCO3 in limestone and determine the effect of heating temperature on the CaCO3 crystal phase in limestone using XRF and XRD methods. XRF test results show that the compounds contained in limestone in Manulai I village are CaO, Nb2O5, Cr2O3, MoO3, In2O3, SnO2, Sb2O3, RuO4, dan Na2O and XRD test results showed that the crystal phase of CaCO3 at a temperature of 5500C to 7500C was in the form of calcite. In limestone calcined at different temperatures, the intensity increases, this can be interpreted that the higher the calcination temperature, the higher the crystallinity.